الآيات والأحاديث الواردة في تفسير سورة الكهف من صحيح الإمام البخاري: دراسة تفسيرية حديثية - Dididk Hariyanto; Md Masm Billah; Muhammad Ali al-Gamidi; Adel M Abdulaziz Al Geriani (USIM Press, 2024)
Vol 7. No. 2 Page (46-68)